La búsqueda de profesionalización en la actividad teatral de Quito (1925-1927) [Estudios] - Aguirre Salas, Alejandro (2023)
The article studies local theatrical groups in Quito between 1925 and 1927, based on a declamation course at the National Music Conservatory. These groups sought to replicate the productive and creative model of professional theatrical companies that consisted of an internationally successful repertoire and the division of archetypal roles among its members, both of which determined their success at the box office. After reflecting on the theater groups’ initial enthusiasm for the creation of a working space and a favorable specialized critique, the contradictions of the model and the limits of the actors’ training and experience in the face of the low demand for shows from a still emerging audience are examined.